Multi-enzyme complex in laying hens diet (Revista de Ciências Agroveterinárias, 2017)
The main purpose of this work was to evaluate the effects of supplementation of laying hen diets with increasing levels of enzymatic complex composed of α-amylase, β-glucanase, cellulase, xylanase, protease and phytase in the forms “on top”, with reductions in the levels of PB, MS, Ca, P available and amino acids. Semi-heavy 384 layers were used with Isa Brown hens, with an initial age of 29 weeks, distributed in six treatments with eight replications, with eight birds per experimental plot, using a completely randomized design (CRD) with sub installments on time (4 periods of 28 days each). The treatments were: Positive Control (PC) 2.750 kcal kg-1 MS, 17.2% PC and 0.41% available P; Negative Control (NC) 2.600 kcal kg-1 MS, 16.7% PC, 0.26% available P; Positive Control + 350 g ton-1 of feed of enzymatic complex (PC350); Negative Control + 250 g ton-1 of feed of enzymatic complex (NC250); Negative Control + 350 g ton-1 of feed of enzymatic complex (NC350) and; Negative Control + 500 g ton-1 of feed of enzymatic complex (NC500). The variables analyzed for growth performance were: feed intake (g bird-1 day-1), egg production (% bird-1 day-1), average egg weight (%) and feed conversion per egg mass (kg kg-1 of feed/eggs). The internal and external quality variables of the analyzed eggs were shell thickness (mm), bark percentages of albumen and yolk, Haugh unit and specific gravity (g cm-3). The addition of enzymatic complex did not interfere in the results of zoo-technical importance or quality of eggs from hens aged 29-44 weeks. Increased consumption of feed/bird/day was enough to supply the reduced nutritional levels of NC diets and maintain balance in the results to the rest of the variables. For some growth performance variables sometimes during the trial period, a negative influence of the inclusion of high levels of enzymatic complex was observed where the NC350 and NC500 diets had a high feed intake and a worst feed conversion than the other diets.
Keywords: Laying poultry; Protease; Pylanase; Phytase; Egg quality.